2009
DOI: 10.1080/09273940802553261
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Segment Involvement in Korean Patients with HLA-B27-Associated Uveitis

Abstract: Patients with posterior segment involvement showed worse visual outcome than patients without posterior involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Several reports on retinal vasculitis in HLA-B27-positive patients were previously published and were considered a part of atypical posterior segment manifestations in HLA-B27-associated uveitis. 2,[4][5][6][7][8][9] From a cohort of 166 patients with HLA-B27-associated uveitis, Rodriguez et al reported 7 (4%) patients with retinal vasculitis, which is in accordance with our findings. 4 The occurrence of retinal vasculitis in HLA-B27-associated disease may in fact even be higher than 3%, as not all our patients with retinal vasculitis were tested for HLA-B27.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several reports on retinal vasculitis in HLA-B27-positive patients were previously published and were considered a part of atypical posterior segment manifestations in HLA-B27-associated uveitis. 2,[4][5][6][7][8][9] From a cohort of 166 patients with HLA-B27-associated uveitis, Rodriguez et al reported 7 (4%) patients with retinal vasculitis, which is in accordance with our findings. 4 The occurrence of retinal vasculitis in HLA-B27-associated disease may in fact even be higher than 3%, as not all our patients with retinal vasculitis were tested for HLA-B27.…”
Section: Discussionsupporting
confidence: 91%
“…HLA-B27-associated uveitis typically presents as a recurrent unilateral acute anterior uveitis (AAU), 1 although posterior segment manifestations in HLA-B27-associated uveitis are regularly reported. [2][3][4] The most common posterior segment manifestations include vitritis, cystoid macular edema (CME), and optic disc leakage. [2][3][4] Occasional cases of retinal vasculitis in HLA-B27-positive patients are also documented, and constitute about 20-25% of those with posterior segment involvement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] The most common findings reported include vitritis, retinal vasculitis, papillitis, epiretinal membrane formation, and CME. As regards the latter manifestation, Uy et al found its frequency in HLA-B27-associated AAU to be 13.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Of these less typical presentations, posterior segment involvement in a patient with HLA-B27-associated uveitis is perhaps most common, and can include vitritis with or without pars plana exudates, optic disc swelling or papillitis, and CME. 46,[49][50][51] Hypotony maculopathy has also been reported in association with severe HLA-B27-associated AU, but is rare. 52,53 It is important to separate genuine inflammatory involvement located in the posterior segment from what can be considered complication of AU, such as CME.…”
Section: Less Common Forms Of Hla-b27-associated Uveitismentioning
confidence: 99%